2009
DOI: 10.1007/s12011-008-8299-0
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Copper and Bone Mineral Density in Osteopenia: An Indicator of Bone Mineral Density in Osteopenic Females

Abstract: Copper concentrations in blood plasma have been determined in 25 osteopenic females using inductively coupled plasma-mass spectrometry. A high degree of correlations has been demonstrated between the copper concentrations in plasma and the bone mineral density of the lumbar spine as measured using dual energy X-ray absorptiometry and quantitative computerized tomography. Results clearly indicate the involvement of copper in bone health and osteopenia. It is further suggested that plasma copper might be useful … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 9 publications
0
13
1
Order By: Relevance
“…Elemental analysis of plasma samples was carried out using a combination of solution-based ICP-AES (Thermo Scientific iCAP 6000) for the determination of Na, Mg, P, S, K, Ca and Fe, and solution-based ICP-MS (Agilent Technologies 7500cs) for the determination of Al, B, Si, Ti, Sc, V, Cr, Mn, Co, Ni, Zn, Cu, Ga, Ge, As, Se, Rb, Sr, Y, Zr, Nb, Mo, Cd, In, Sn, Sb, Te, Cs, Ba, La, Ce, Nd, Hf, W, Tl, Pb, Bi, Th, and U as reported earlier [13,14]. Sample preparation for elemental analysis consisted of dissolving a known mass (accurately weighed to three significant figures in gram mass) of sample in a mixture of high purity (quartz sub-boiling redistilled) nitric acid and hydrogen peroxide 20% v/v, in 50 ml volume, acid-washed polyethylene tubes, under individual reflux in a water bath for 24 h. A series of certified reference materials (CRMs), (IAEA-A-13 animal blood; NIST SRM 1547 peach leaves; NIST SRM 1515 apple leaves and NIST SRM 1573a tomato leaves) was dissolved using the same procedure.…”
Section: Methodsmentioning
confidence: 85%
“…Elemental analysis of plasma samples was carried out using a combination of solution-based ICP-AES (Thermo Scientific iCAP 6000) for the determination of Na, Mg, P, S, K, Ca and Fe, and solution-based ICP-MS (Agilent Technologies 7500cs) for the determination of Al, B, Si, Ti, Sc, V, Cr, Mn, Co, Ni, Zn, Cu, Ga, Ge, As, Se, Rb, Sr, Y, Zr, Nb, Mo, Cd, In, Sn, Sb, Te, Cs, Ba, La, Ce, Nd, Hf, W, Tl, Pb, Bi, Th, and U as reported earlier [13,14]. Sample preparation for elemental analysis consisted of dissolving a known mass (accurately weighed to three significant figures in gram mass) of sample in a mixture of high purity (quartz sub-boiling redistilled) nitric acid and hydrogen peroxide 20% v/v, in 50 ml volume, acid-washed polyethylene tubes, under individual reflux in a water bath for 24 h. A series of certified reference materials (CRMs), (IAEA-A-13 animal blood; NIST SRM 1547 peach leaves; NIST SRM 1515 apple leaves and NIST SRM 1573a tomato leaves) was dissolved using the same procedure.…”
Section: Methodsmentioning
confidence: 85%
“…Chaudhri et al (Chaudhri et al 2009) found a linear relationship between serum Cu values and bone density in post-menopausal women. By contrast, the men in our study with low serum Cu levels had BMD similar to those of the reference group.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of Cu in bone health has been studied in the context of Cu deficiency and osteoporosis (Palacios 2006; Chaudhri et al 2009; Lowe et al 2002). Chaudhri et al (Chaudhri et al 2009) found a linear relationship between serum Cu values and bone density in post-menopausal women.…”
Section: Discussionmentioning
confidence: 99%
“…Many epidemiological studies with mixed findings have investigated the associations between serum copper levels, cardiovascular disease and neurodegenerative diseases [9] , [10] , [11] , [12] . However, the association between copper status and the risk of osteoporosis and related diseases has been examined by only few observational studies and remains controversial because of inconsistent results [13] , [14] , [15] , [16] , [17] , [18] . Sadeghi et al.…”
Section: Introductionmentioning
confidence: 99%